2021
DOI: 10.1002/cbic.202100249
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune Glycoprotein Lactoferrin Represses the Helicobacter pylori cag Type IV Secretion System

Abstract: Chronic infection with Helicobacter pylori increases risk of gastric diseases including gastric cancer. Despite development of a robust immune response, H. pylori persists in the gastric niche. Progression of gastric inflammation to serious disease outcomes is associated with infection with H. pylori strains which encode the cag Type IV Secretion System (cag T4SS). The cag T4SS is responsible for translocating the oncogenic protein CagA into host cells and inducing pro‐inflammatory and carcinogenic signaling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…A study of 48 term and preterm infants found that the number of fecal bifidobacteria and lactobacilli correlates significantly with fecal Lf concentrations 3 days after delivery, suggesting that Lf may promote the growth of beneficial intestinal microbiota ( 52 ). Although Lf inhibits the growth of harmful bacteria, some researchers have found large amounts of Lf in the resected stomachs of patients with gastritis, speculating that H. pylori takes up iron through specific Lf receptors, and more importantly, Lf may play a major role in the virulent effects of H. pylori infection ( 53 ).…”
Section: Physicochemical Properties and Applications Of Lactoferrinmentioning
confidence: 99%
“…A study of 48 term and preterm infants found that the number of fecal bifidobacteria and lactobacilli correlates significantly with fecal Lf concentrations 3 days after delivery, suggesting that Lf may promote the growth of beneficial intestinal microbiota ( 52 ). Although Lf inhibits the growth of harmful bacteria, some researchers have found large amounts of Lf in the resected stomachs of patients with gastritis, speculating that H. pylori takes up iron through specific Lf receptors, and more importantly, Lf may play a major role in the virulent effects of H. pylori infection ( 53 ).…”
Section: Physicochemical Properties and Applications Of Lactoferrinmentioning
confidence: 99%
“…29−36 Human milk harbors a variety of antimicrobial molecules that can inhibit the growth and viability of a variety of pathogenic microbes as well as immune-modulating molecules that influence inflammation responses to invading pathogens. 34 Our recent work and the work of others has demonstrated that the human milk glycoprotein lactoferrin has antimicrobial and antibiofilm activities against A. baumannii and other bacteria, including S. agalactiae, S. aureus, and Pseudomonas aeruginosa. 35−39 In addition to the proteinaceous components of milk, the human milk glycome is also of particular interest, as components within this population of molecules have been associated with strong protection against infection by enteric pathogens.…”
Section: ■ Discussionmentioning
confidence: 92%
“…The utility of human milk as a prebiotic that can protect against a variety of infections has been well demonstrated in the literature. ,, Infants whose primary source of nutrition, which is derived from human breast milk, have enhanced protection against diarrhea, respiratory infection, urinary tract infection, ear infection, necrotizing enterocolitis (NEC), and specifically, infection with Escherichia coli , Clostridioides difficile , and Campylobacter jejuni . Human milk harbors a variety of antimicrobial molecules that can inhibit the growth and viability of a variety of pathogenic microbes as well as immune-modulating molecules that influence inflammation responses to invading pathogens . Our recent work and the work of others has demonstrated that the human milk glycoprotein lactoferrin has antimicrobial and antibiofilm activities against A. baumannii and other bacteria, including S. agalactiae , S. aureus , and Pseudomonas aeruginosa . In addition to the proteinaceous components of milk, the human milk glycome is also of particular interest, as components within this population of molecules have been associated with strong protection against infection by enteric pathogens …”
Section: Discussionmentioning
confidence: 99%
“…Lu et al's subsequent report showed that the increased levels of LF in gastric tissue were caused by H. pylori colonization, as demonstrated by the Mongolian gerbil's model [48]. The Mongolian gerbil is a rodent model that recapitulates many features of H. pyloriinduced gastric disease in humans [49].…”
Section: Intragastric Lactoferrin and H Pylori Colonizationmentioning
confidence: 99%